Effectiveness of Canva Learning Media Using the Discovery Learning Model at SDN 37 Pasar Bukit - Kasmayulia, Riza; Reinita, Reinita; Mansurdin, Mansurdin; Waldi, Atri (Journal of Basic Education Research, 2025)
Purpose of the study: The purpose of this study was to determine the effectiveness of Canva learning media in improving the learning outcomes of 5th grade students at elementary school 37 Pasar Bukit, Linggo Sari Baganti District, Pesisir Selatan Regency. Methodology: This development research employs the ADDIE model. The stages of the ADDIE development model are Analysis, Design, Development, Implementation, and Evaluation. The data collection methods used in this study were interviews, observation, tests, and documentation. The pre-test is conducted before using the Canva learning media, and the post-test is administered after the learning process using Canva with 20 multiple choice questions. Main Findings: The research findings indicate that, prior to the implementation of the learning media, 5 students achieved mastery while 13 students did not. However, after utilizing the instructional media, the percentage of student learning mastery at elementary schoo 37 Pasar Bukit increased by 88.88%, meaning 16 out of 18 students showed improvement, and 2 students maintained their results. With a mastery percentage of 88.88%, this signifies that 16 students achieved mastery, while 2 did not. Therefore, it is evident that the use of Canva based learning media with the Discovery Learning model can enhance student learning outcomes. Novelty/Originality of this study: This research involves years of research, new research objects and research subjects that have never been studied before and developing learning media created using the Canva application with the researcher's own voice recordings without dubbing.